Preparation method of biomass aggregate lightweight wall impervious concrete and concrete
By using surfactant pretreatment and paraffin-silane composite emulsion vacuum impregnation process, combined with core-shell structured functional materials, the problem of balancing hydrophilicity and lightweight properties with high impermeability in biomass aggregate concrete has been solved. This has achieved efficient hydrophobicity and improved concrete strength, forming a triple impermeability system that is hydrophobic, dense, and barrier-resistant.
Patent Information
- Application Number
- CN202511690009.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-01-23
AI Technical Summary
Existing biomass aggregate concrete has a rich pore structure and hydrophilic properties that result in weak interfacial bonding, making it difficult to balance lightweight and high impermeability. Furthermore, the low utilization rate of industrial waste residue has failed to effectively improve the microstructure density of the concrete.
By employing surfactant pretreatment and paraffin-silane composite emulsion vacuum impregnation process, combined with core-shell structure functional materials, the hydrophobic components penetrate and the vacuum environment eliminates air resistance within the pores, forming a strong bond between the hydrophobic material and the aggregate pore walls. This, along with the core-shell structure and active admixtures filling the micropores, constructs a triple impermeable system that is hydrophobic, dense, and barrier-resistant.
It significantly improves the impermeability grade of biomass aggregate lightweight wall impermeable concrete to above P12, reduces water absorption to below 8%, maintains lightweight characteristics, and improves the strength and thermal insulation performance of concrete.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, in particular to a preparation method of biomass aggregate lightweight wall body impermeable concrete and the concrete. BACKGROUND
[0002] With the continuous improvement of building energy saving and environmental protection requirements, biomass aggregate (such as rice husk, straw derived material) as an important direction of resource utilization of agricultural waste is widely used in the preparation of lightweight concrete. Biomass aggregate has the characteristics of small density and excellent thermal insulation performance, which can effectively reduce the dry apparent density of concrete and improve the thermal insulation effect of wall body, conforming to the development trend of green building.
[0003] However, the existing biomass aggregate concrete has significant technical bottlenecks: first, biomass aggregate itself has rich pore structure and strong hydrophilic characteristics, which is easy to absorb mixing water of concrete, resulting in weak interface bonding between aggregate and cement matrix, forming connected pores, which seriously affects the impermeability of concrete; second, it is difficult to balance lightweight and high strength, high impermeability, and conventional biomass concrete often sacrifices strength to ensure lightweight properties, or increases cement content to improve strength, resulting in excessive density and decreased thermal insulation performance; third, the resource utilization rate of industrial waste slag (such as steel slag, slag) and river silt is low, and the synergistic optimization effect with biomass aggregate has not been formed, and the internal microstructure of concrete is difficult to be effectively compacted. SUMMARY
[0004] In view of the deficiencies of the prior art, the present application provides a preparation method of biomass aggregate lightweight wall body impermeable concrete and the concrete, which adopts surface active agent pretreatment and paraffin-silane composite emulsion vacuum impregnation process. The surface active agent can reduce the surface tension of the emulsion, promote the penetration of hydrophobic components into the pores of the aggregate, and eliminate the air resistance in the pores in the vacuum environment, so that the hydrophobic material and the pore wall of the aggregate form a firm combination, the hydrophobic effect is more durable, and the strength and impermeability of the concrete are improved.
[0005] To achieve the above purpose, the present application provides the following technical scheme: a preparation method of biomass aggregate lightweight wall body impermeable concrete, comprising the following steps: Step (1): pretreatment of biomass aggregate: mixing and pressing rice husk or straw biomass raw materials with sintering agent to form biomass-based wood ceramic spherical particles in a vacuum furnace; Step (2): hydrophobic treatment of aggregate surface: the biomass-based wood ceramic spherical particles obtained in step (1) are pretreated with a surface active agent solution, and then vacuum impregnated with paraffin-silane composite emulsion; Step (3): Preparation of functional material: mixing river sludge and industrial waste residue according to the proportion, adding hydrogen peroxide pore-forming agent, preparing porous core material, then coating with steel slag, slag and desulfurization gypsum mixture to form shell layer, obtaining core-shell structure functional material; Step (4): Concrete mixing: mixing biomass aggregate after surface hydrophobic treatment, core-shell structure functional material, sulphoaluminate cement, coal cinder, silica fume, fly ash, polypropylene fiber, polycarboxylate superplasticizer, thickening agent, air entraining agent and water according to the proportion; Step (5): Curing and forming: pouring the mixed concrete into the wallboard mold, curing for 6 hours at room temperature until the cement is completely hardened, to obtain the preparation method of biomass aggregate lightweight wall body impermeable concrete and the concrete.
[0006] Preferably, in step (1), the biomass raw material is at least one of rice husk, straw and corn stalk; the sintering agent is clay mineral, and the mass ratio of biomass raw material to sintering agent is (3-5):1.
[0007] Preferably, in step (2), the mass ratio of paraffin to silane in the paraffin-silane composite emulsion is (1-2):1, the vacuum degree of vacuum impregnation treatment is -0.05 to -0.08 MPa, and the treatment time is 20-40 minutes.
[0008] Preferably, in step (3), the core material is composed of the following raw materials in mass parts: river sludge 20-90 parts, hydrogen peroxide 1-15 parts, rice husk ash 10-50 parts, sodium hydroxide 1-12 parts, and desulfurization gypsum 5-40 parts; the shell material is composed of the following raw materials in mass parts: steel slag 10-100 parts, slag 5-40 parts, desulfurization gypsum 5-30 parts, and polyvinyl alcohol 2-13 parts.
[0009] Preferably, in step (4), the raw materials of the concrete include, by mass percentage: biomass aggregate 13.5-33.8%, core-shell structure functional material 4.0-17.0%, sulphoaluminate cement 38.6-43.3%, coal cinder 8.0-18.0%, silica fume 4.0-10.0%, fly ash 4.2-10.0%, water 12.0-22.0%, polypropylene fiber 0.5-1.0%, polycarboxylate superplasticizer 0.5-1.5%, thickening agent 0.1-0.5%, and air entraining agent 0.1-0.4%; the total mass percentage of each component is 100%.
[0010] Preferably, the amount of core-shell structure functional material added to the concrete is 30%-50% of the mass of biomass aggregate.
[0011] Preferably, the preparation of the core-shell structure functional material in step (3) adopts a sintering-free process, and is formed by a hydrothermal synthesis reaction under the condition of 85-100 DEG C for 24-48 hours.
[0012] Preferably, the preparation method of the biomass aggregate lightweight wall impermeable concrete and the impermeable grade of the concrete are not less than P12, the water absorption is not more than 8%, the dry apparent density is not more than 1500 kg / m 3 , the 7-day compressive strength of the concrete is not less than 25 MPa, the 28-day compressive strength is not less than 35 MPa, and the thermal conductivity is not more than 0.35 W / (m.K).
[0013] Preferably, the surface active agent in step (2) is sodium dodecyl sulfate or sodium dodecyl benzene sulfonate, the mass concentration of the solution is 0.5%-1.5%, the pretreatment mode is spraying treatment, and the spraying amount is 2%-5% of the mass of the biomass aggregate.
[0014] The biomass aggregate lightweight wall impermeable concrete, the preparation method of the biomass aggregate lightweight wall impermeable concrete, the impermeable grade is not less than P12, the water absorption is not more than 8%, the dry apparent density is not more than 1500 kg / m 3 , the 7-day compressive strength of the concrete is not less than 25 MPa, the 28-day compressive strength is not less than 35 MPa, and the thermal conductivity is not more than 0.35 W / (m.K).
[0015] Compared with the prior art, the present application provides a preparation method of biomass aggregate lightweight wall impermeable concrete and concrete, which has the following beneficial effects: by adopting surface active agent pretreatment and paraffin-silane composite emulsion vacuum impregnation process, the surface active agent can reduce the surface tension of the emulsion, promote the penetration of the hydrophobic component into the internal pores of the aggregate, and eliminate the air resistance in the pores in the vacuum environment, so that the hydrophobic material and the pore wall of the aggregate are firmly combined, and the hydrophobic effect is more durable. Compared with the traditional surface coating, the water absorption of the aggregate is reduced from 15%-25% to below 8%, and the interface defect problem caused by the hydrophilicity of the biomass aggregate is solved from the root.
[0016] The core adopts a porous river channel silt-rice hull ash composite material to provide lightweight characteristics; the shell layer is composed of active materials such as steel slag and slag, which generates a secondary hydration reaction with the cement matrix to form hydrated calcium silicate (C-S-H) gel to densify the interface transition zone, and the physical coating effect of the shell layer enhances the bonding force between the aggregate and the matrix. The material not only realizes the resource utilization of river channel silt and industrial waste slag, but also cooperatively improves the strength and impermeability of the concrete.
[0017] The hydrophobic biomass aggregate blocks the water adsorption channel, the core-shell functional material densifies the interface structure, the active admixture such as silica ash and fly ash fills the micro-pore, and the small closed air bubbles introduced by the air-entraining agent block the capillary pore connection, so that a triple anti-permeation system of hydrophobic, dense and blocking is formed, and the impermeability grade of the concrete is improved from P6-P8 to P12 or above. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the present application.
[0019] The present application provides a preparation method of biomass aggregate lightweight wall impermeable concrete and a technical solution of the concrete, in particular: The silane specifically refers to an organic silane with a hydrophobic function, including but not limited to gamma-aminopropyl triethoxysilane, gamma-glycidyl ether propyl trimethoxysilane, methyl trimethoxysilane and the like. The core technical feature is that it can form a hydrophobic film with paraffin and can chemically react with the hydroxyl group on the surface of the biomass aggregate. In the embodiment of the specification, gamma-aminopropyl triethoxysilane (purity ≥98%) is used, which is a preferred scheme, but other functionally equivalent silane compounds are not excluded. Those skilled in the art can select according to conventional hydrophobic treatment requirements, and the protection scope can be clearly protected without additional limitations.
[0020] The process for forming the shell layer is as follows: the shell layer raw materials (steel slag, slag, desulfurization gypsum, polyvinyl alcohol) are mixed and then water is added to prepare a slurry with a water-solid ratio of 0.3-0.4; The rolling coating method or the immersion coating method is used: the core material particles are placed in a granulator, the shell layer slurry is sprayed and rolled to uniformly cover the surface of the particles, or the core material is directly immersed in the shell layer slurry for 30 minutes, and then the excess slurry is removed by sieving; the thickness of the shell layer after coating is controlled to be 1-2 mm, and then the shell layer is cured and formed by hydrothermal synthesis reaction. This process is a conventional preparation method of core-shell structure materials in the art.
[0021] The concentration type of the surfactant solution: according to the conventional expression habit in the field of concrete materials, the concentration is the mass concentration (mass fraction), that is, 0.5-1.5 g of sodium dodecyl sulfate or sodium dodecyl benzene sulfonate is contained in every 100 g of aqueous solution. This expression is consistent with the conventional understanding of those skilled in the art, and no additional limitations are required.
[0022] Key parameters of biomass aggregate sintering: based on the embodiments of the specification and the known knowledge of wood ceramic preparation, the core parameter range of the sintering process is: sintering temperature: 800-900℃ (ensure carbonization of biomass raw materials and formation of ceramic phase with sintering agent); heating rate: 5-10℃ / min (avoid particle cracking); holding time: 2-3h (ensure sufficient sintering); vacuum degree: -0.08~-0.09MPa (exclude gas generated during sintering). These parameters are necessary conditions to achieve the performance of "biomass-based wood ceramic".
[0023] Reaction conditions of hydrothermal synthesis: the pressure condition of hydrothermal synthesis is "autogenous pressure", that is, after the reaction kettle is closed, the pressure formed by the evaporation of water in the kettle at a temperature of 85-100℃ (usually 0.1-0.3MPa). This condition is a conventional operation of hydrothermal synthesis process in the art.
[0024] Biomass raw materials: rice husk (moisture content ≤10%, crushed to particle size ≤2mm), straw (corn stalk, crushed to particle size ≤2mm); Sintering agent: clay mineral (montmorillonite content ≥80%, particle size ≤0.075mm); Surfactant: sodium dodecyl sulfate (industrial grade, purity ≥95%); Paraffin-silane composite emulsion: paraffin (melting point 58-60℃), silane (γ-aminopropyl triethoxysilane, purity ≥98%), emulsion solid content 40%; River silt: dredged silt from a river, moisture content 60%, dried and crushed to particle size ≤0.15mm; Industrial waste residue: steel slag (converter steel slag, specific surface area 400m 2 / kg), slag (granulated blast furnace slag, specific surface area 450m 2 / kg); Cementitious material: sulphoaluminate cement (42.5 grade, initial setting time ≤30min), desulfurization gypsum (industrial grade, purity ≥90%); Active admixture: silica fume (specific surface area ≥20000m 2 / kg, SiO2 content ≥90%), fly ash (grade II, specific surface area 350m 2 / kg); Admixture: polycarboxylic acid water reducer (solid content 40%, water reducing rate ≥30%), thickening agent (hydroxypropyl methyl cellulose, viscosity 100,000mPa・s), air entraining agent (rosin thermopolymer, air content ≥10%); Others: polypropylene fiber (length 12mm, diameter 20μm), hydrogen peroxide (industrial grade, concentration 30%), sodium hydroxide (industrial grade, purity ≥96%), polyvinyl alcohol (polymerization degree 1750±50).
[0025] Example 1 Biomass aggregate pretreatment: rice husk and clay minerals were mixed at a mass ratio of 3:1, pressed into spherical particles, and heated to 800℃ at a rate of 5℃ / min in a vacuum furnace (vacuum degree -0.08 MPa) for 2h to obtain biomass-based wood ceramic particles; Hydrophobic treatment: 0.5% (mass concentration) sodium dodecyl sulfate solution was prepared and sprayed on the pretreated biomass aggregate at a mass ratio of 2%; paraffin-silane composite emulsion (mass ratio 1:1) was impregnated for 20min at a vacuum degree of -0.05 MPa and dried at 60℃; Core-shell functional material preparation: core material (mass parts): river silt 20 parts, hydrogen peroxide 1 part, rice husk ash 10 parts, sodium hydroxide 1 part, desulfurization gypsum 5 parts; shell material (mass parts): steel slag 10 parts, slag 5 parts, desulfurization gypsum 5 parts, polyvinyl alcohol 2 parts; hydrothermal synthesis (85℃, autogenous pressure) curing for 24h, and crushing to 3-5mm; Concrete mixing: ingredient (total 100%) by mass percentage: biomass aggregate 13.5%, core-shell functional material 4.1% (30% of the mass of biomass aggregate), sulphoaluminate cement 38.6%, cinder 8.0%, silica fume 4.0%, fly ash 4.2%, water 12.0%, polypropylene fiber 0.5%, polycarboxylate superplasticizer 0.5%, thickening agent 0.1%, air entraining agent 0.1%; dry mixing for 2min, wet mixing for 5min; Curing and molding: room temperature curing for 6h, demolding, and standard curing until the test age.
[0026] Example 2 Biomass aggregate pretreatment: rice husk + corn stalk (mass ratio 1:1) and clay minerals were mixed at a mass ratio of 4:1, pressed into spherical particles, and heated to 850℃ at a rate of 8℃ / min in a vacuum furnace (vacuum degree -0.085 MPa) for 2.5h; Hydrophobic treatment: 1.0% (mass concentration) sodium dodecyl sulfate solution was prepared and sprayed on the pretreated biomass aggregate at a mass ratio of 3%; paraffin-silane composite emulsion (mass ratio 1.5:1) was impregnated for 30min at a vacuum degree of -0.065 MPa and dried at 60℃; Core-shell functional material preparation: core material (mass parts): river silt 55 parts, hydrogen peroxide 8 parts, rice husk ash 30 parts, sodium hydroxide 6 parts, desulfurization gypsum 22 parts; shell material (mass parts): steel slag 55 parts, slag 22 parts, desulfurization gypsum 17 parts, polyvinyl alcohol 7 parts; hydrothermal synthesis (90℃, autogenous pressure) curing for 36h, and crushing to 4-6mm; Concrete mixing: ingredient (total 100%) by mass percentage: biomass aggregate 23.6%, core-shell functional material 9.4% (40% of biomass aggregate mass), sulphoaluminate cement 40.9%, cinder 13.0%, silica fume 7.0%, fly ash 7.2%, water 17.0%, polypropylene fiber 0.7%, polycarboxylate superplasticizer 1.0%, thickening agent 0.3%, air entraining agent 0.2%; dry mixing 2 min, wet mixing 6 min; Curing and molding: same as Example One.
[0027] Example Three Biomass aggregate pretreatment: straw and clay minerals are mixed at a mass ratio of 5:1, pressed into spherical particles, and heated to 900℃ at a rate of 10℃ / min in a vacuum furnace (vacuum degree -0.09MPa) for 3h; Hydrophobic treatment: 1.5% (mass concentration) sodium dodecyl sulfate solution is prepared and sprayed on the pretreated biomass aggregate at a mass percentage of 5%; paraffin-silane composite emulsion (mass ratio 2:1) is immersed for 40min at a vacuum degree of -0.08MPa and dried at 60℃; Core-shell functional material preparation: core material (mass parts): river silt 90 parts, hydrogen peroxide 15 parts, rice husk ash 50 parts, sodium hydroxide 12 parts, desulfurized gypsum 40 parts; shell material (mass parts): steel slag 100 parts, slag 40 parts, desulfurized gypsum 30 parts, polyvinyl alcohol 13 parts; hydrothermal synthesis (100℃, autogenous pressure) curing for 48h, and crushing to 6-8mm; Concrete mixing: ingredient (total 100%) by mass percentage: biomass aggregate 33.8%, core-shell functional material 16.9% (50% of biomass aggregate mass), sulphoaluminate cement 43.3%, cinder 18.0%, silica fume 10.0%, fly ash 10.0%, water 22.0%, polypropylene fiber 1.0%, polycarboxylate superplasticizer 1.5%, thickening agent 0.5%, air entraining agent 0.4%; dry mixing 2 min, wet mixing 8 min; Curing and molding: same as Example One.
[0028] Example Four Biomass aggregate pretreatment: rice husk + straw (mass ratio 2:1) and clay minerals are mixed at a mass ratio of 4:1, pressed into spherical particles, and heated to 850℃ at a rate of 8℃ / min in a vacuum furnace (vacuum degree -0.085MPa) for 2.5h; Hydrophobic treatment: 1.2% (mass concentration) sodium dodecyl sulfate solution is prepared and sprayed on the pretreated biomass aggregate at a mass percentage of 4%; paraffin-silane composite emulsion (mass ratio 1.5:1) is immersed for 35min at a vacuum degree of -0.07MPa and dried at 60℃; Core-shell functional material preparation: same as Example Two; Concrete mixing: ingredient proportioning (total 100%) by mass percentage: biomass aggregate 28.5%, core-shell functional material 12.8% (45% of the mass of the biomass aggregate), sulphoaluminate cement 41.5%, coal cinder 15.5%, silica fume 8.0%, fly ash 8.5%, water 20.0%, polypropylene fiber 0.8%, polycarboxylate superplasticizer 1.2%, thickening agent 0.4%, air entraining agent 0.3%; dry mixing for 2 min, wet mixing for 7 min; Curing and molding: same as Example One.
[0029] Comparative Example One Except that step 2 omits hydrophobic treatment (only pre-treatment with water spraying), the remaining preparation steps and raw material proportions are completely consistent with Example Two.
[0030] Comparative Example Two Step 2 is changed to: configure the same proportion of paraffin-silane composite emulsion, use a brush to coat the surface of the biomass aggregate (coating amount is consistent with the impregnation absorption amount of Example Two), and dry at 60°C; the remaining preparation steps and raw material proportions are completely consistent with Example Two.
[0031] Comparative Example Three No core-shell structure functional material is added in step 4, and the remaining raw materials are adjusted by mass percentage as follows: biomass aggregate 23.6%, sulphoaluminate cement 44.0%, coal cinder 14.0%, silica fume 7.6%, fly ash 7.8%, water 18.3%, polypropylene fiber 0.7%, polycarboxylate superplasticizer 1.1%, thickening agent 0.3%, air entraining agent 0.2% (total 100%), and the preparation steps are completely consistent with Example Two.
[0032] Comparative Example Four Step 3 is changed to only prepare the core material (same as the core formula of Example Two), without shell coating, and directly added as a functional material; the remaining preparation steps and raw material proportions are completely consistent with Example Two.
[0033] Comparative Example Five The core-shell functional material content in step 4 is 20% of the mass of the biomass aggregate (i.e. 4.7% by mass percentage), and the remaining raw materials are adjusted by mass percentage as follows: biomass aggregate 23.6%, core-shell functional material 4.7%, sulphoaluminate cement 41.8%, coal cinder 13.3%, silica fume 7.2%, fly ash 7.4%, water 17.5%, polypropylene fiber 0.7%, polycarboxylate superplasticizer 1.0%, thickening agent 0.3%, air entraining agent 0.2% (total 100%), and the preparation steps are completely consistent with Example Two.
[0034] Comparative Example Six The rest of the raw materials are adjusted in mass percentage as follows: biomass aggregate 23.6%, core-shell functional material 9.4%, sulphoaluminate cement 43.0%, coal cinder 14.0%, fly ash 14.2%, water 17.5%, polypropylene fiber 0.7%, polycarboxylate superplasticizer 1.0%, thickening agent 0.3% (total 100%) without adding air entraining agent and silica ash in step 4, and the preparation steps are completely consistent with example two.
[0035] Preparation method of biomass aggregate lightweight wall impermeable concrete, and concrete test standard and method Impermeability grade test standard: GB / T50082-2009 "Standard for testing methods of long-term performance and durability of ordinary concrete", 6.2 step-by-step pressure method; Test equipment and test pieces Equipment: concrete impermeability instrument in line with JG / T249 standard, precision 0.01 MPa, with 6 test sites; Test pieces: 6 Φ175mm*Φ185mm*150mm cylinders, standard curing for 28 days; Detailed test steps Test piece preparation: one day before the test, take out the test piece, dry the surface (moisture content ≤3%) and wipe it clean; melt the paraffin (or paraffin-pine sealing agent), evenly roll coat the test piece with a layer (thickness 1-2mm); after cooling, check the integrity of the sealing layer to ensure that there is no bubble and no cracking; Instrument preparation: start the impermeability instrument, open the 6 test site valves, make the water seep out of the test site pit, and exclude air from the pipeline; close the valve, install the sealed test piece on the test site, tighten the nut but not pre-tighten; open the valve, observe the water seepage from the test piece periphery, then tighten the nut to ensure good sealing; Pressure test: initial water pressure is set to 0.1 MPa, and pressure is stabilized for 24 hours (to exclude installation stress); then increase by 0.1 MPa every 8 hours, and gradually increase the pressure; observe the test piece end face at any time, and record the time and pressure when the first seepage appears for each test piece; Result calculation and evaluation: formula: impermeability grade=10*H-1; H: water pressure (MPa) when the third of the 6 test pieces appears seepage; Evaluation rule: when the maximum water pressure of 4 of the 6 test pieces appears seepage, the impermeability grade is determined as 10 times the maximum water pressure; accurate to integer, such as P12, P14, etc. Water absorption test standard: GB / T50081-2019 "Standard for testing methods of physical and mechanical properties of concrete", new water absorption test method; Test equipment and test piece: equipment: electronic balance (accuracy 0.01 g), constant temperature water tank (20±2℃), oven (105±5℃), dryer; test piece: 3 150mmx150mmx150mm cubes, standard curing for 28 days; Detailed test steps Test piece pretreatment: take the test piece out of the curing room, wipe the surface with a wet cloth, weigh (W1) to 0.01 g; measure the size of the test piece, calculate the surface area and volume (for volume water absorption calculation, optional); Saturation process: place the test piece in a 20±2℃ constant temperature water tank, with water level above the test piece by more than 50mm; soak for 48 hours (or until constant weight, with the difference between the two weighings <0.1%); take out the test piece and gently wipe off the surface moisture with a wet cloth (saturated surface dry state), immediately weigh (W2) to 0.01 g; Drying measurement: place the test piece in a 105±5℃ oven and dry to constant weight (with the difference between the two weighings <0.1%); take out and cool to room temperature in a desiccator, weigh (W0) to 0.01 g; Result calculation and evaluation Formula: water absorption rate=(W2-W0) / W0x100%; W0: test piece oven-dried mass (g), W2: test piece saturated surface-dry mass (g); Evaluation rules: take the arithmetic mean of the three test piece values as the water absorption rate value, accurate to 0.1%; if the maximum or minimum value differs from the intermediate value by >5%, eliminate the extreme value and take the intermediate value; non-standard test pieces need to be multiplied by a correction factor (determined according to the cross-sectional size); Dry apparent density test standard: GB / T50081-2019 "Standard for test methods of physical and mechanical properties of concrete", 2.1.14 item apparent density definition; Test equipment and test piece Equipment: electronic balance (accuracy 0.01 kg), oven (105±5℃), dryer, measuring ruler (accuracy 1mm); test piece: 3 150mmx150mmx150mm cubes, standard curing for 28 days; Detailed test steps Test piece preparation: take the test piece out of the curing room, number and measure the size (accurate to 1mm), calculate the volume (V); weigh (original mass m_r) to 0.01 kg; Drying measurement: place the test piece in a 105±5℃ oven and dry to constant weight (with the difference between the two weighings <0.1%); take out and cool to room temperature in a desiccator, weigh (oven-dried mass m_d) to 0.01 kg; Result calculation and evaluation Formula: dry apparent density=m_d / Vx1000; m_d: Drying mass of the specimen (kg), V: Total volume of the specimen (m³) 3 ); Evaluation rule: The arithmetic mean of the measurements of 3 specimens is taken as the dry apparent density value, accurate to 10 kg / m³. 3 If the maximum or minimum value differs from the average value by more than 5%, the outlier is removed and the calculation is repeated. Compressive strength test standard: GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", 5 Compressive strength test; Test equipment and test specimens Equipment: Compression testing machine (accuracy ±1%, range to ensure failure load is within 20%-80%). Test specimens: 3 cubes of 150mm×150mm×150mm (7 days / 28 days of age), standard curing; Detailed test steps Specimen preparation: Remove specimens from the curing room according to their age, wipe off surface moisture, measure dimensions (accurate to 1 mm), and calculate the bearing area A (mm²). 2 ); Inspect the appearance of the specimens. There must be no defects such as chipped edges, cracks, etc., otherwise the specimens will be rejected. Test procedure: Place the specimen in the center of the lower pressure plate of the testing machine, ensuring that the bearing surface is perpendicular to the top surface of the mold; adjust the testing machine so that the center of the specimen is aligned with the center of the upper and lower pressure plates (eccentricity ≤ 2 mm); continuously and uniformly load at the specified rate: strength ≤ C30: 0.3~0.5 MPa / s, C30~C60: 0.5~0.8 MPa / s, ≥ C60: 0.8~1.0 MPa / s, continue loading until the specimen fails, and record the maximum failure load P (N); Results Calculation and Evaluation Formula: Compressive strength = P / A; P: Destructive load (N), A: Bearing area (mm²) 2 ); Evaluation rules: The arithmetic mean of the three test specimens is taken as the compressive strength value, accurate to 0.1 MPa; if the maximum or minimum value differs from the average value by more than 15%, the outlier value is discarded and the average of the other two values is taken; non-standard size specimens need to be multiplied by a size correction factor (e.g., 100mm cube × 0.95, 200mm cube × 1.05). Thermal conductivity testing standard: GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of thermal insulation materials - protective hot plate method"; Test equipment and test specimens Apparatus: guarded hot plate thermal conductivity meter (accuracy ± 5%), constant temperature control system (accuracy ± 0.1℃), measuring scale (accuracy 1mm); Specimen: 2 pieces of 300mm x 300mm x 30mm plates (or Φ300mm x 30mm cylinders), dried to constant weight in an oven at 105±5℃; Detailed test procedure Specimen preparation: Take the specimen from the curing room, dry it to constant weight in an oven at 105±5℃ (the difference between the two weightings is <0.1%); measure the specimen dimensions (to the nearest 1mm), calculate the heat transfer area (A) and thickness (d); check the surface flatness of the specimen and, if necessary, polish it; Test procedure: Place the specimen between the hot plate and the cold plate, ensuring close contact and avoiding thermal bridges and air gaps; set the hot plate temperature T_H=30℃ and the cold plate temperature T_L=10℃, forming a temperature difference (ΔT=T_H-T_L) of 20℃; start the temperature control system, maintain a stable temperature difference, and reach steady-state heat transfer (at least 12 hours, temperature fluctuation <0.1℃); record the heat flow (q), hot plate temperature (T_H), cold plate temperature (T_L), and specimen thickness (d); Result calculation and evaluation Formula: Thermal conductivity = q x d / (A x ΔT); q: heat flow (W), d: specimen thickness (m), A: heat transfer area (m 2 ), ΔT: cold-hot plate temperature difference (℃); Evaluation rules: Take the arithmetic mean of the two measured values as the thermal conductivity value, accurate to 0.01 W / (m·K); if the difference between the two measured values is >10%, retest is required.
[0036] The performance of the biomass aggregate lightweight wall body impermeable concrete obtained in the examples and comparative examples was tested, including impermeability grade, water absorption rate (%), dry apparent density (kg / m 3 ), 7-day compressive strength (MPa), 28-day compressive strength (MPa), and thermal conductivity (W / (m·K)). The specific test results are shown in the table below.
[0037] As can be seen from the comparison of Example 2 and Comparative Example 1 and Comparative Example 2, without hydrophobic treatment, the hydrophilic nature of the biomass aggregate leads to a water absorption rate of 18.3% and an impermeability grade of only P6, with a 28-day compressive strength of 28.7MPa; surface coating treatment improves it, but the water absorption rate is still 12.5%, the impermeability grade is P8, and the strength improvement is limited; the vacuum impregnation process of the present application reduces the water absorption rate to 6.2%, improves the impermeability grade to P14, and significantly improves the strength, proving that deep hydrophobic treatment can solve the interface defects caused by the hydrophilic nature of biomass aggregate from the root, and is one of the core factors for improving impermeability.
[0038] It can be seen from the comparison of Example 2 and Comparative Examples 3, 4 that when there is no core-shell material, the impermeability grade of the concrete is P7, and the 28-day compressive strength is 30.3 MPa, and the weak interface bonding leads to performance degradation; when there is only a single core material, the impermeability grade is only P8, and the strength is 32.8 MPa due to the lack of an active shell layer; and when there is a core-shell structure material, the impermeability grade is improved to P14, and the strength is up to 39.5 MPa through the synergistic effect of core lightening and shell secondary hydration, which proves that the core-shell structure design can simultaneously optimize the lightweight characteristics, interface structure and density of the concrete.
[0039] It can be seen from the comparison of Example 2 and Comparative Examples 5, 6 that when the content of the core-shell material is less than 30%, the impermeability grade decreases from P14 to P10, and the strength decreases by 6 MPa, which shows that sufficient content is a prerequisite for function; when there is no air entraining agent and silica fume, the impermeability grade decreases to P9, and the strength is 31.6 MPa, which proves that the pore filling and blocking effect of active admixtures and air entraining agents is an important part of the synergistic impermeability system.
[0040] Through the combination of deep hydrophobic treatment, core-shell functional materials and a synergistic impermeability system, the impermeability grade of the concrete is improved from P6-P8 in the prior art to P12-P15, the water absorption is reduced from 15%-25% to 5.7%-7.8%, and the 28-day compressive strength is ≥35 MPa under the condition of a lightweight dry apparent density ≤1500 kg / m 3 .
[0041] The above is only a specific embodiment of the present application, but the technical features of the present application are not limited thereto. Any simple change, equivalent replacement or modification made on the basis of the present application to solve the same technical problem and achieve the same technical effect is also covered by the protection scope of the present application.
Claims
1. A method for preparing a biomass aggregate lightweight wall impermeable concrete, characterized in that: The method comprises the following steps: Step (1): pretreatment of biomass aggregate: rice husk or straw biomass raw material is mixed with sintering agent and pressed into shape, and then sintered in a vacuum furnace to obtain biomass-based woodceramics spherical particles; Step (2): surface hydrophobic treatment of aggregate: the biomass-based woodceramics spherical particles obtained in step (1) are pretreated with a surfactant solution, and then vacuum impregnated with a paraffin-silane composite emulsion; Step (3): preparation of functional material: river sludge and industrial waste slag are mixed in a certain proportion, and hydrogen peroxide is added as a pore-forming agent to prepare a porous core material, and then a shell layer is formed by coating the core material with a mixture of steel slag, slag and desulfurization gypsum to obtain a core-shell structure functional material; Step (4): mixing of concrete: the surface hydrophobic treated biomass aggregate, the core-shell structure functional material, sulphoaluminate cement, coal ash, silica fume, fly ash, polypropylene fiber, polycarboxylic acid water reducer, thickening agent, air entraining agent and water are mixed and stirred according to the proportion; Step (5): curing and forming: the uniformly mixed concrete is poured into a wallboard mold, and cured at room temperature for 6 hours until the cement is completely hardened to obtain a method for preparing a biomass aggregate lightweight wall body impermeable concrete.
2. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 1, characterized in that: In step (1), the biomass raw material is at least one of rice husk, straw and corn stalk; the sintering agent is clay mineral, and the mass ratio of biomass raw material to sintering agent is 3-5:
1.
3. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 1, characterized in that: In step (2), the mass ratio of paraffin to silane in the paraffin-silane composite emulsion is 1-2:1, the vacuum degree of vacuum impregnation treatment is -0.05 to -0.08 MPa, and the treatment time is 20-40 minutes.
4. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 1, characterized in that: In step (3), the core material is composed of the following raw materials in parts by mass: river sludge 20-90 parts, hydrogen peroxide 1-15 parts, rice husk ash 10-50 parts, sodium hydroxide 1-12 parts, and desulfurization gypsum 5-40 parts; the shell material is composed of the following raw materials in parts by mass: steel slag 10-100 parts, slag 5-40 parts, desulfurization gypsum 5-30 parts, and polyvinyl alcohol 2-13 parts.
5. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 1, characterized in that: In step (4), the raw materials of the concrete include, by mass percentage: biomass aggregate 13.5-33.8%, core-shell structure functional material 4.0-17.0%, sulphoaluminate cement 38.6-43.3%, coal ash 8.0-18.0%, silica fume 4.0-10.0%, fly ash 4.2-10.0%, water 12.0-22.0%, polypropylene fiber 0.5-1.0%, polycarboxylic acid water reducer 0.5-1.5%, thickening agent 0.1-0.5%, and air entraining agent 0.1-0.4%; the total mass percentage of each component is 100%.
6. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 5, characterized in that: The amount of the core-shell structure functional material added to the concrete is 30%-50% of the mass of the biomass aggregate.
7. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 1, characterized in that: In step (3), the core-shell structure functional material is prepared by a sintering-free process, and is cured at 85-100℃ for 24-48 hours by hydrothermal synthesis reaction.
8. The method for preparing biomass aggregate lightweight wall impermeable concrete according to claim 1, characterized in that: The surface active agent in step (2) is sodium dodecyl sulfate or sodium dodecyl benzene sulfonate, the mass concentration of the solution is 0.5%-1.5%, the pretreatment mode is spraying treatment, and the spraying amount is 2%-5% of the mass of the biomass aggregate.
9. A concrete prepared according to the method of any one of claims 1 to 8, wherein: The preparation method of the biomass aggregate lightweight wall body impermeable concrete has impermeable grade not less than P12, water absorption not more than 8%, and dry apparent density not more than 1500 kg / m 3 The concrete has 7-day compressive strength not less than 25 MPa, 28-day compressive strength not less than 35 MPa, and thermal conductivity not more than 0.35 W / (m.K).
Citation Information
Patent Citations
Fabricated thermal insulation wallboard material containing rice husk-based wood ceramic lightweight aggregate and preparation method thereof
CN108640618A
Technique for preparing lightweight aggregate for thermal insulation wallboard by using rice husk and sulphate aluminum cement
CN108658486A
Core-shell type solid waste-based functional aggregate as well as preparation method and application thereof
CN119430846A
Solid-waste-based phase-change energy-storage lightweight aggregate applied to marine concrete and preparation method of solid-waste-based phase-change energy-storage lightweight aggregate
CN120328903A
Kind of high impermeability low thermal conductivity inorganic lightweight foam concrete and preparation method
US20240124367A1
Cited By
Sophorolipid modified recycled aggregate, phase change concrete and preparation method thereof
CN122079521A